2020
DOI: 10.1097/md.0000000000023239
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of massage in the treatment of restless legs syndrome

Abstract: Background: Restless legs syndrome (RLS), known as a kind of neurological disease, is prevalent but easy to be ignored. Studies have demonstrated that massage therapy can effectively reduce the symptoms of patients with RLS and improve their quality of life. However, the efficacy of massage therapy for RLS is still controversial. Therefore, this protocol aims to evaluate the reliability of massage therapy in treating RLS in a thorough way. Methods: We will search releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Those without neuropathy showed a high percentage of No RLS in them. RLS causes creepy-crawly sensations in the legs and gets resolved by activity 3 . RLS causes an ant sensation in the legs, an irresistible urge to move the legs restlessness and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those without neuropathy showed a high percentage of No RLS in them. RLS causes creepy-crawly sensations in the legs and gets resolved by activity 3 . RLS causes an ant sensation in the legs, an irresistible urge to move the legs restlessness and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Restless leg syndrome (RLS) is a sensorimotor sleep-related movement disorder characterized by a strong desire to move one's legs and an uncomfortable sensation in the lower extremities 1 . The prevalence of RLS in the general population is 5 to 15% 2,3 . The unpleasant sensation in the legs improved with movement.…”
Section: Introductionmentioning
confidence: 99%
“…8b Previously, we reported the nucleophilic difluoro-(phenylthio)methylation of a series of electrophiles with PhSCF 2 H using t-BuOK or KOH as the base and found that PhSCF 2 − can readily react with ketones. 9 In view of this, we envisioned that the combination of an aromatic thiolate anion (ArS − ) and difluorocarbene (to in situ generate ArSCF 2 − ) would provide a novel method for nucleophilic difluoro-(arylthio)methylations. However, our initial attempt to difluoromethylate ketones using 2-PySCF 2 − generated in situ from 2-PyS − and a difluorocarbene source such as sodium chlorodifluoroacetate (SCDA) failed to afford the desired product (Scheme 1c).…”
mentioning
confidence: 99%